2004
DOI: 10.1128/aem.70.1.137-144.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression inSaccharomyces cerevisiaeof a Laccase Gene from the AscomyceteMelanocarpus albomyces

Abstract: The lac1 gene encoding an extracellular laccase was isolated from the thermophilic fungus Melanocarpus albomyces. This gene has five introns, and it encodes a protein consisting of 623 amino acids. The deduced amino acid sequence of the laccase was shown to have high homology with laccases from other ascomycetes. In addition to removal of a putative 22-amino-acid signal sequence and a 28-residue propeptide, maturation of the translation product of lac1 was shown to involve cleavage of a C-terminal 14-amino-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 45 publications
5
47
0
Order By: Relevance
“…N-and C-terminal peptide sequence analyses of the purified recombinant laccase produced by T. reesei showed that this host is able to perform both of the processing steps correctly. When M. albomyces laccase was expressed in S. cerevisiae, the production levels were enhanced both by using yeast alpha-factor prosequence in the expression construct and by introducing a stop codon into the laccase cDNA at the C-terminal processing site (Kiiskinen & Saloheimo, 2004). This indicated indirectly that baker's yeast was not able to perform either of the processing steps of the laccase efficiently.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…N-and C-terminal peptide sequence analyses of the purified recombinant laccase produced by T. reesei showed that this host is able to perform both of the processing steps correctly. When M. albomyces laccase was expressed in S. cerevisiae, the production levels were enhanced both by using yeast alpha-factor prosequence in the expression construct and by introducing a stop codon into the laccase cDNA at the C-terminal processing site (Kiiskinen & Saloheimo, 2004). This indicated indirectly that baker's yeast was not able to perform either of the processing steps of the laccase efficiently.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that M. albomyces laccase is processed at both its N-and C-termini (Kiiskinen & Saloheimo, 2004). The C-terminal processing is of special interest, because the truncated C-terminus protrudes inside the enzyme, potentially forming a plug to an O 2 /H 2 O exchange tunnel leading to the active site (Hakulinen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations